2019
DOI: 10.1101/750232
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retention and predictors of attrition among patients who started antiretroviral therapy in Zimbabwe’s National Antiretroviral Therapy Programme between 2012 and 2015

Abstract: 21Background 22 The last evaluation to assess outcomes for patients receiving antiretroviral therapy (ART) 23 through the Zimbabwe public sector was conducted in 2011, covering the 2007-2010 cohorts. 24 The reported retention at 6, 12, 24 and 36 months were 90. 7%, 78.1%, 68.8% and 64.4%, 25 respectively. We report findings of a follow up evaluation for the 2012-2015 cohorts to assess 26 the implementation & impact of recommendations from this prior evaluation. 27 Methods 28A nationwide retrospec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…Although there is overwhelming support for the UTT strategy, evident by the adoption of the strategy by most countries [ 35 ], the current study findings and those of others [ 31 , 40 ] suggest that a delay is required for individuals who test HIV positive to accept the diagnosis. There is need to provide psychosocial preparation and readiness assessment to newly diagnosed HIV-positive individuals before ART initiation under UTT [ 39 ]. This is necessary for individuals to make informed decision whether or not to attend a clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is overwhelming support for the UTT strategy, evident by the adoption of the strategy by most countries [ 35 ], the current study findings and those of others [ 31 , 40 ] suggest that a delay is required for individuals who test HIV positive to accept the diagnosis. There is need to provide psychosocial preparation and readiness assessment to newly diagnosed HIV-positive individuals before ART initiation under UTT [ 39 ]. This is necessary for individuals to make informed decision whether or not to attend a clinic.…”
Section: Discussionmentioning
confidence: 99%
“…We included variables that were associated with LFTU up in the bivariate analysis at p value of 0.05. We also included variables such as gender, age, and clinical data including CD4 count and WHO staging based on a documented association with loss to follow up in literature [ 25 , 39 ]. A p-value < 0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…Among patients who initiated ART in the last quarter of 2018 in South Africa, for example, 30% were reported as lost to follow up by six months 9 . In Zimbabwe, retention in care improved significantly between 2010 and 2015 except for patients in their first six months 10 . Beyond the impact on individual morbidity and mortality, early losses from care are associated with internalized stigma, leading to social isolation, fear of disclosure, and discrimination, which potentially compound the inherent challenges in returning to care 11 13 .…”
Section: Introductionmentioning
confidence: 99%
“…viral load suppression, was unavailable. Previous studies showed that the retention on ART was high, but that access to viral load monitoring and viral load suppression remained suboptimal [33][34][35].…”
Section: Limitationsmentioning
confidence: 99%